Knowledge, and attitude, and decisional conflict regarding biologics among patients with inflammatory bowel disease: a cross-sectional study - Li, Qianqian; Xia, Chenmei; Chen, Chunxiao; Jiang, Yi; Jin, Lingxiao; Zhang, Jianmei; Wu, Linfeng; Jiang, Li; Chen, Xia (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the knowledge, attitude, and decisional conflict regarding biologic treatments among patients with inflammatory bowel disease (IBD) in China.MethodsThis cross-sectional study included IBD patients recruited at the authors’ hospital between July 2023 and January 2024. Data were collected using a self-administered questionnaire covering demographic characteristics, knowledge, attitude, and decisional conflict (measured by the Decisional Conflict Scale).ResultsA total of 405 IBD patients participated, with 45.9% aged 30–49 years and 64% male. The average knowledge score was 6.03 ± 2.98 (possible range: 0–11), and the average attitude score was 24.36 ± 3.32 (possible range: 8–40). Among them, 60 (14.8%) patients exhibited significant decisional conflict. Spearman correlation analysis revealed a positive association between knowledge and attitude scores (r = 0.554, p < 0.001). Multivariate analysis revealed that being ≥ 50 years old, having ulcerative colitis, never having used biologics, and experiencing significant decisional conflict were associated with lower knowledge scores. Higher knowledge scores, a monthly income between 10,000–20,000 RMB, never having used biologics, and significant decisional conflict were associated with lower attitude.ConclusionOlder age, ulcerative colitis, lack of prior biologic use, and decisional conflict were associated with lower knowledge and lower attitude toward biologics among IBD patients. Targeted educational interventions may help reduce decisional conflict and improve patients’ attitudes toward biologic therapy.